(untitled) (Sains Humanika, 2016)
Islam Hadhari Islam is another policy implemented after the adaptation of ‘Islamic Values’ introduced by Prime Minister Abdullah Badawi post-election of 2004 General Election in Malaysia. It is a comprehensive approach to human development, society and state of Malaysia based on the perspective of Islamic civilization. In order to achieve these goals, the government outlines 10 fundamental principles that are considered suitable to be implemented in the context of Malaysia. Since the launch of Islam Hadhari, the government has been working hard to promote and implement Islam Hadhari over the globe. As for this purpose, JAKIM as federal level religious institution was entrusted to coordinate all activities related to the implementation of Islam Hadhari in Malaysia. This article attempts to examine the development of the organization and generally evaluate the implementation of an organizational structure in JAKIM especially in mobilizing Islamic Hadhari which the establishment has covered both, the federal and state levels. However, there are still some problems due to the organization of Islam Hadhari is basically in deficient compared to other organizations with the addition of the engagement under other existing organization, whether either at the federal or state level. This situation led to the failure to achieve the goals set by the activities. Thus, it is nothing more than a political rhetoric to repeat the routine activities in the form of lectures and publications than specific activities to build a glorious generation.